Fe@Hierarchical BEA zeolite catalyst for MW-assisted alcohol oxidation reaction: a greener approach - Andrade, Marta A. (2020)
The aim of this study was to investigate the catalytic activity of hybrid materials of iron supported on hierarchical zeolites in the oxidation reaction of 1-phenylethanol to acetophenone. A greener approach was considered for the preparation of the catalyst and performance of the oxidation reaction. Hierarchical BEA zeolite samples were obtained from an alkaline and a subsequent acid treatment. The materials were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and nitrogen adsorption at -196 degrees C. An iron salt was incorporated onto the hierarchical zeolites by mechanochemical grinding and the catalytic performance of the prepared materials was evaluated towards the microwave assisted oxidation reaction of 1-phenylethanol. The catalyst obtained by Fe immobilization on sample modified by 0.2 M NaOH followed by acid treatment (Fe@BEA0.2AT) is the most promising material with 35% yield and 56% selectivity to acetophenone, allowing five reuse cycles without significant loss of activity and selectivity.